2017
DOI: 10.1002/jcp.26257
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GHET1 predicts poor prognosis in hepatocellular carcinoma and promotes cell proliferation by silencing KLF2

Abstract: Hepatocellular carcinoma (HCC) has been identified as one of the leading causes of cancer-related death worldwide. Recently, long non-coding RNAs (lncRNAs) attract much attention of researchers, and they are demonstrated to be dysregulated in a variety of cancers, including HCC. LncRNA gastric carcinoma high expressed transcript 1 lncRNA GHET1 is found to be dysregulated in gastric cancer (GC). However, its clinical value and potential biological function in HCC remains unclear. In this study, the expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 31 publications
(33 reference statements)
1
65
0
Order By: Relevance
“…7,8 Many lncRNAs have been reported in HCC progression. 11 Overexpression of the lncRNA SNHG16 can inhibit HCC proliferation by sponging hsa-miR-93. 11 Overexpression of the lncRNA SNHG16 can inhibit HCC proliferation by sponging hsa-miR-93.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Many lncRNAs have been reported in HCC progression. 11 Overexpression of the lncRNA SNHG16 can inhibit HCC proliferation by sponging hsa-miR-93. 11 Overexpression of the lncRNA SNHG16 can inhibit HCC proliferation by sponging hsa-miR-93.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 For example, the lncRNA GHET1 promotes HCC cell proliferation and can predict poor prognosis in HCC via inhibiting KLF2. 11 Overexpression of the lncRNA SNHG16 can inhibit HCC proliferation by sponging hsa-miR-93. 12 In addition, knockdown of ANRIL is able to repress HCC progression through modulating miR-122-5p.…”
Section: Introductionmentioning
confidence: 99%
“…Previous genome-wide screening studies using lncRNA datasets from GEO and TCGA in lung cancer [55,56], gastric cancer [44] and breast cancer [57,58] also identified cell cycle-related lncRNAs. Several studies reported that dysregulation of specific lncRNAs in HCC cell lines caused cell cycle arrest and induced apoptosis, and affected the prognosis of HCC [59,60]. KEGG enrichment analysis revealed a significant enrichment in the PPAR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…KLF2 was reported to inhibit colorectal cancer cell proliferation through enhancing HIF‐1α/Notch‐1 signal pathway . It is worthy to note that KLF2 could be downregulated by GHET1 . Therefore, we speculated KLF2 and HIF‐1α/Notch‐1 signal pathway might be involved in the mechanism of GHET1 regulating PC.…”
Section: Introductionmentioning
confidence: 90%